Tahfidz Al-Qur’an Learning Strategies from Bandura's Perspective in Islamic Educational Institutions in Bontang City - Khumaini Rosadi; Mukhamad Ilyasin; Siti Julaiha (UIN Sunan Gunung Djati Bandung, 2025)
Learning to memorize the Qur'an is an important part of Islamic education that requires effective strategies to be able to form a generation of memorizers of the Qur'an who excel spiritually and intellectually. This study aims to reveal the learning strategy for memorizing the Qur'an from the perspective of Albert Bandura's theory in two Islamic educational institutions in Bontang City, namely MAN Bontang (state) and SMA IT YABIS (private). A qualitative approach with a multi-site study design was used in this study, with data collection techniques in the form of observation, in-depth interviews, and documentation. Bandura's theory was used as the basis for analysis, especially in the aspects of modeling (exemplary behavior of teachers and peers), self-efficacy (student self-confidence), and reinforcement (social reinforcement). The results of the study showed that the learning strategy for memorizing the Qur'an in both institutions prioritized a personal approach, intensive mentoring, and strengthening the Qur'anic character through mentoring activities, joint muroja'ah, and a structured reward system. MAN Bontang excels in systemic reinforcement through the madrasah program, while SMA IT YABIS excels in an individual approach and family involvement. In conclusion, the learning strategy for memorizing the Al-Qur'an based on Bandura's theory has been proven to be able to significantly increase students' motivation, self-confidence, and memorization achievements, and is relevant to be applied in the context of Islamic education in both state and private institutions by adjusting the characteristics of the institution.